INVESTIGATING AUTISTIC TRAITS AND SIMPLE SENSORY PROCESSING. Issue 10 (9th September 2014) - Sugden, Peter; Simmons, David; McGonigle, David
Abstract : Introduction: The diagnoses of classic autism and Asperger's syndrome are thought to represent various points on an 'autistic spectrum' that also extends into the neurotypical population. Indeed those with high levels of autistic traits perform more like those with Autism Spectrum Disorder (ASD), than those with low levels, in various psychological tests. There is evidence that those with ASD have enhanced simple sensory processing. Furthermore, there is evidence that the amount of autistic traits is correlated to self-reported sensory over-responsivity in the neurotypical population. A relationship between autistic traits and objective measures of sensory processing has not been investigated. Method: 'Vibrotactile frequency discrimination' and 'pure tone pitch discrimination' were measured as objective markers of sensory processing in 23 students. These were compared with autistic traits measured using The Autism Quotient (AQ) Questionnaire. Results: There were no significant correlations between AQ scores and markers of sensory processing. Therefore the level of autistic traits appears to be unrelated to simple sensory processing in the neurotypical population. Discussion: The relationship between AQ score and sensory over-reponsiveness may not translate into one between AQ score and sensory processing. Larger sample sizes may be needed to detect this likely subtle correlation.